ECONOMETRIC MODELS FOR ASSESSING FINANCIAL SUSTAINABILITY IN THE ERA OF DIGITAL INNOVATION - Oramov, Jahongir (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The article proposes to use econometric models to analyze factors affecting financial stability in the new digital economy. Based on empirical evidence, the authors explore the impact of digital innovation on the financial system, identify key factors that determine the level of financial sustainability, and make recommendations for improving financial stability management in the new digital format.